Competing for Influence in Networks through Strategic Targeting - Margherita Comola; Agnieszka Rusinowska; Marie Claire Villeval (Institute of Labor Economics (IZA), 2024)
We experimentally investigate how players with opposing views compete for influence through strategic targeting in networks. We varied the network structure, the relative influence of the opponent, and the heterogeneity of the nodes' initial opinions. Although most players adopted a best-response strategy based on their relative influence, we also observed behaviors deviating from this strategy, such as the tendency to target central nodes and avoid nodes targeted by the opponent. Targeting is also affected by affinity and opposition biases, the strength of which depends on the distribution of initial opinions.
Keywords: C91; D85; D91; 330; network; influence; targeting; competition; laboratory experiment